Measurement of endotracheal tube cuff pressure: Instrumental versus conventional method - Khan, Mueen Ullah (Saudi J Anaesth, 2016)
OBJECTIVE: To evaluate the conventional practice of endotracheal tube (ETT) cuff inflation and pressure measurement as compared to the instrumental method. STUDY DESIGN: Prospective observational study. PLACE AND DURATION OF STUDY: Department of Anaesthesia, King Saud University Hospital, Riyadh, Saudi Arabia (June 2014–July 2014). METHODS: A total of 100 adult patients were observed according to the syringe size used Group-1 (10 ml) and Group-2 (20 ml) for ETT cuff inflation in general anesthesia. Patients with anticipated difficult intubation, risk for aspiration, known anatomical laryngotracheal abnormalities, and emergency cases were excluded. Trachea was intubated with size 8 or 8.5 mm and 7.0 or 7.5 mm ETT in male and female patients respectively. The ETT cuff was inflated with air by one of the anesthesia technician. Cuff pressures were measured using aneroid manometer. ETT cuff pressure of 20–30 cm of water was considered as standard. RESULTS: In 69% of the patients, the cuff pressure measurements were above the standard. Age (P = 0.806), weight (P = 0.527), height (P = 0.850), and gender (P = 1.00) were comparable in both groups. The mean cuff pressure in Group-1 and Group-2 was 32.52 ± 6.39 and 38.90 ± 6.60 cm of water (P = 0.001). The cuff inflation with 20 ml syringe resulted in higher cuff pressure as compared to 10cc syringe 37.73 ± 4.23 versus 40.74 ± 5.01 (86% vs. 52%, P = 0.013). CONCLUSION: The conventional method for ETT cuff inflation and pressure measuring is unreliable. As a routine instrumental cuff pressure, monitoring is suggested.